Efektivitas Jus Jambu Biji Merah Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester III di Puskesmas Karang Anyar - Desi Safitri; Linda Puspita; Nopi Anggista Putri; Wisnu Probo Wijayanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Zinc deficiency anemia is a global health problem, especially in pregnant women. Management to deal with the occurrence of anemia in pregnant women is done through various approaches, including the provision of fortified foods. Fortified foods given can be in the form of fruit, one of which is red guava fruit. This study aims to analyze the effectiveness of red guava juice consumption on increasing hemoglobin levels in third trimester pregnant women at Karang Anyar South Lampung Health Center. This research design uses pre-experiment with one group pre test and post test, the research was conducted at Karang Anyar Health Center, South Lampung Regency in December 2024. Researchers collected data for 14 consecutive days. Researchers conducted a paired sample t test. The results showed that the average Hb before administration was 9.4 gr/dl, the average Hb after administration was 9.9 gr/dl. There is an effect of giving red guava juice on Hemoglobin (Hb) levels of anemic pregnant women at the Karang Anyar South Lampung Health Center (p-value = 0.000). Researchers suggest that health workers can socialize the benefits of red guava juice as a complementary therapy accompanied by the fulfillment of nutrition during pregnancy.